Effectiveness Test of Bay Leaf Ethanol Extract as Antihyperuricemia Invivo - Hilda S; Rosnike Merly Panjaitan; Nurul Hidayah (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
The imbalance between high production and low excretion of uric acid in the body causes hyperuricemia, which can lead to gout. This disease is the second largest after stroke in Indonesia. Conventional therapy is not free from adverse effects. The tendency of society to go back to nature and the government's "Saintifikasi Jamu" program are efforts to explore safer alternative therapies. One of the plants that has the potential as an antihyperuricemia is bay leaves (Syzygium polyanthum Walp.). The purpose of this study is to optimize the use of scientifically based bay leaves as an antihyperuricemia agent. The research method used is experimental with a pre-posttest design . A total of 20 mice were divided into 5 test groups (induction, comparison, bay leaf extract group (EEDS) with doses of 100 mg/kgBW, 200 mg/kgBW, and 400 mg/kgBW. The effectiveness of antihyperuricemia was tested by inducing mice with 1% chicken liver juice and potassium oxonate. Uric acid levels were measured at T1, T7 and T14 days of the study using a Blood Uric Acid Meter. All groups of test extract doses showed effectiveness as agents to lower uric acid levels significantly compared to the induction group (p<0.05). The potential effectiveness of the antihyperuricemia extract showed an effect that was not statistically different from the comparison (allopurinol) (p>0.05) at all measurement points. The conclusion of this study shows that bay leaf ethanol extract has the potential as an antihyperuricemia agent, where a dose of 100 mg/kgBW showed the best effectiveness as an antihyperuricemia Keywords: Bay Leaves, Extract, Chicken Liver, Potassium Oxonate, Uric Acid